The Concept of Religious Character Education from the Perspectives of Buya Hamka and KH Ahmad Dahlan and Its Implications for Early Childhood Education in the Digital Era - M. Masyhuri; Benny Prasetiya; Muhammad Alfi Syahrin (Immortalis Journal of Interdisciplinary Studies, 2026)
This study aims to analyze the conceptual framework of Buya Hamka’s and KH. Ahmad Dahlan’s thoughts on religious character education for early childhood in the digital era. Using a qualitative library research approach with hermeneutic analysis, this research examines the primary works of both scholars and contemporary academic literature. The findings reveal that Hamka’s thought emphasizes the spiritual dimension centered on tazkiyatun nafs (purification of the soul), faith awareness, and the cultivation of inner morality as a moral safeguard amid digital disruption. Meanwhile, Dahlan’s thought focuses on Qur’anic social praxis through the values of amar ma’ruf nahi munkar, rationality, and social responsibility in the ethical use of technology. The synthesis of both perspectives results in a religious character education model built upon three dimensions: spiritual, socio-rational, and digital adaptability. This model underscores the integration of faith, social ethics, and Islamic digital literacy as the foundation for early childhood education relevant to the moral challenges of the digital age. The study contributes to the development of an integrative Islamic education theory and provides implications for designing PAUD curricula based on adaptive religious values.